"Good Politicians": Experimental Evidence on Motivations for Political Candidacy and Government Performance - Saad Gulzar; Muhammad Yasir Khan (Institute of Labor Economics (IZA), 2023)
How can we motivate good politicians – those that will carry out policy that is responsive to citizens' preferences – to enter politics? In a field experiment in Pakistan, we vary how political office is portrayed to ordinary citizens. We find that emphasizing prosocial motives for holding political office instead of personal returns – such as the ability to help others versus enhancing one's own respect and status – raises the likelihood that individuals run for office and that voters elect them. It also better aligns subsequent policies with citizens' preferences. We further find that social versus personal messaging only matters when randomly delivered in a public setting, suggesting that the extrinsic calculus is particularly important in candidacy decisions. Taken together, the results demonstrate that how politics is perceived in democracies shapes political entry as well as policy outcomes.
Keywords: O12; D72; H75; 330; political selection; policy-making; state capacity